Alterações ultrassonográficas da glândula Tireoide em pacientes com obesidade graus II e III - RODRIGUES, Taliane Jardim Lima (2019)
Introduction: Thyroid abnormalities have been associated with obesity and many mechanisms have been proposed to explain this association. Obesity has been associated with increased thyroid volume, increased thyroid stimulating hormone (TSH), worsening of insulin resistance (IR), with a consequent increase in insulin-1- like growth factor (IGF-1), and still changes in secretions of adipocytokines / cytokines, being potential factors for the development and progression of thyroid cancer. There is no recommendation for the screening of thyroid nodules by ultrasonography (US) in obese individuals. Objective: The present study aims to identify the frequency of thyroid ultrasonographic changes in obese patients correlating findings with insulin-1-like growth factor (IGF-1), C-reactive protein (PCR) and clinical-laboratory IR. Materials and Methods: A cross-sectional study that included 67 patients with class II and III obesity and 44 controls with normal BMI, from 18 to 60 years. All participants were submitted to an anamnesis, physical examination, thyroid ultrasonography and laboratory analysis. Results: Obese patients had higher levels of homeostatic model assessment - insulin resistance (HOMA-IR) and PCR (P <0.001). The distribution of thyroid findings, with borderline probability (P = 0.054), showed that the control group had a higher normal thyroid frequency (54.5%) and obesity group had the heterogeneous standard (38.8%). There were no statistically significant differences in the thyroid pattern among patients with or without IR (P = 0.129). Obese patients and patients with IR presented statistically higher thyroid volume than controls (P <0.001). Seventeen (25.4%) patients in the obesity group and 11 (25%) patients in the control group had at least one nodule in the thyroid, with indication of FNA in 6 (35.3%) and 1 (9.1%), respectively. Low IGF-1 was more frequent among patients with IR (14.5%; P = 0.052).The level of PCR was statistically higher in the heterogeneous pattern than in those with normal thyroid (P <0.05). Conclusions: This study did not observe a positive correlation between the variables insulin resistance and IGF-1 levels with the presence of nodules or other thyroid changes, but the thyroid findings of patients with obesity showed a greater thyroid volume in this group, with a heterogeneous pattern of the gland more evident. The obesity group had higher levels of insulin resistance and PCR, which may be directly involved with the findings. Some patients had lower IGF-1 levels, mainly the category with IR. PCR was the only biomarker that correlated with heterogeneous findings.